Individual Optimization of Contrast Media Injection Protocol at Hepatic Dynamic Computed Tomography Using Patient-Specific Contrast Enhancement Optimizer. Issue 2 (March 2020) - Matsumoto, Yoriaki; Higaki, Toru; Arataki, Keiko; Masuda, Takanori; Sato, Tomoyasu; Fukumoto, Wataru; Nakamura, Yuko; Tatsugami, Fuminari; Awai, Kazuo
Abstract : Objective: We developed a patient-specific contrast enhancement optimizer (p-COP) that can exploratorily calculate the contrast injection protocol required to obtain optimal enhancement at target organs using a computer simulator. Appropriate contrast media dose calculated by the p-COP may minimize interpatient enhancement variability. Our study sought to investigate the clinical utility of p-COP in hepatic dynamic computed tomography (CT). Methods: One hundred thirty patients (74 men, 56 women; median age, 65 years) undergoing hepatic dynamic CT were randomly assigned to 1 of 2 contrast media injection protocols using a random number table. Group A (n = 65) was injected with a p-COP-determined iodine dose (developed by Higaki and Awai, Hiroshima University, Japan). In group B (n = 65), a standard protocol was used. The variability of measured CT number (SD) between the 2 groups of aortic and hepatic enhancement was compared using the F test. In the equivalence test, the equivalence margins for aortic and hepatic enhancement were set at 50 and 10 Hounsfield units (HU), respectively. The rate of patients with an acceptable aortic enhancement (250–350 HU) for the diagnosis of hypervascular liver tumors was compared using the χ 2 test. Results: The mean ± SD values of aortic and hepatic enhancement were 311.0 ± 39.9 versus 318.7 ± 56.5 and 59.0 ± 11.5 versus 58.6 ± 11.8 HU in groups A and B, respectively. Although the SD for aortic enhancement was significantly lower in group A ( P = 0.006), the SD for hepatic enhancement was not significantly different ( P = 0.871). The 95% confidence interval for the difference in aortic and hepatic enhancement between the 2 groups was within the range of the equivalence margins. The number of patients with acceptable aortic enhancement was significantly greater in group A than in group B ( P < 0.01). Conclusions: The p-COP software reduced interpatient variability in aortic enhancement and obtained acceptable aortic enhancement at a significantly higher rate compared with the standard injection protocol for hepatic dynamic CT.